2016
DOI: 10.1038/nature17399
|View full text |Cite|
|
Sign up to set email alerts
|

Mitochondrial ROS regulate thermogenic energy expenditure and sulfenylation of UCP1

Abstract: Brown adipose tissue (BAT) can dissipate chemical energy as heat through thermogenic respiration, which requires uncoupling protein 1 (UCP1)1,2. Thermogenesis from BAT and beige adipose can combat obesity and diabetes3, encouraging investigation of factors that control UCP1-dependent respiration in vivo. Herein we show that acutely activated BAT thermogenesis is defined by a substantial increase in mitochondrial reactive oxygen species (ROS) levels. Remarkably, this process supports in vivo BAT thermogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
342
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 364 publications
(359 citation statements)
references
References 51 publications
15
342
0
2
Order By: Relevance
“…Evidence in support of a robust role for UCP1-mediated uncoupling in the regulation of ROS production in vitro has been provided (6,7,41), as have findings suggesting a limited role for UCP1 activity in controlling ROS in vitro (8,(42)(43)(44). Importantly, UCP1 appears to play a role in regulating BAT redox tone in vivo (9), and acute adrenergic stimulation in vivo drives ROS production to support UCP1-dependent thermogenesis (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence in support of a robust role for UCP1-mediated uncoupling in the regulation of ROS production in vitro has been provided (6,7,41), as have findings suggesting a limited role for UCP1 activity in controlling ROS in vitro (8,(42)(43)(44). Importantly, UCP1 appears to play a role in regulating BAT redox tone in vivo (9), and acute adrenergic stimulation in vivo drives ROS production to support UCP1-dependent thermogenesis (10).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is becoming increasingly evident that in specific respiratory states, UCP1 can reduce reactive oxygen species (ROS) levels in vitro (4)(5)(6)(7)(8)(9). The mitochondrial ETC is a major source of ROS production in the cell, and ROS play important roles in physiology and pathophysiology (10)(11)(12). Reverse electron transport (RET) through mitochondrial complex I is a key mechanism by which ROS are generated in vivo (11,13).…”
mentioning
confidence: 99%
“…24 Indeed, during acute or chronic cold acclimation in rodents, an elevation in ROS generation and a shift toward a more oxidized environment was observed in BAT and was associated with mitochondrial proliferation. [25][26][27][28] Furthermore, agents known to deplete glutathione (GSH) such as buthionine sulfoximine (BSO) increased the expression of PGC-1a both in WAT and in BAT. 29 In addition, ROS in the form of H 2 O 2 was shown to directly induce the expression of PGC-1a and PGC-1b in brown-fat fibroblasts through a mechanism involving the Cre-binding protein (CREB).…”
Section: Adsod2 Ko Increases Energy Expenditure and Protects Against Diomentioning
confidence: 99%
“…11). Other studies have reported that this feedback mechanism does not exist (12)(13)(14) (18). Although some critiques remain (19), the issue of whether specific ROS-mediated UCP1 modifications possess physiological relevance may only be settled by expanding analysis, e.g., introducing critical ROS-modified amino acids using in vivo CRISPR/ Cas approaches.…”
mentioning
confidence: 99%
“…The answer is not clear so far. An UCP1 ortholog, distinct from its paralogs UCP2 and UCP3, must have existed before the divergence of lobe-and ray-finned vertebrates more than 420 million years ago because UCP1 is found (18). In the wild-type condition, increased ROS levels are mitigated by higher UCP1 activity (9, 10).…”
mentioning
confidence: 99%